2019
DOI: 10.1002/app.47566
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional architecture of absorbers for enhancement of the absorbing properties of MWNTs

Abstract: The microwave absorbers, which can attenuate and dissipate the incident electromagnetic wave, have attracted much more attentions due to their great potential applications in military stealth and civil healthcare. In this study, the three‐dimensional (3D) architecture absorber of multiwalled carbon nanotubes@polystyrene (MWNTs@PS) was designed and synthesized by the combination of PS microspheres with MWNTs via self‐assembly of electrostatic adsorption. The morphology and dispersity of absorbers were character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…For example, Zhang et al have designed the 3D multiwalled CNTs@polystyrene (MWCNTs/PS) through selfassembly of electrostatic adsorption, which showed a broad effective bandwidth. 16 rGO/MWCNTs/Fe 3 O 4 composites fabricated by Zhang et al exhibited enhanced EMW absorption performance composites compared to the composite without MWCNTs. 25 Mo et al reported the 3D CNTs@TiO 2 sponge by hydrolysis and heat treatment method, which exhibited the desired reflection loss.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, Zhang et al have designed the 3D multiwalled CNTs@polystyrene (MWCNTs/PS) through selfassembly of electrostatic adsorption, which showed a broad effective bandwidth. 16 rGO/MWCNTs/Fe 3 O 4 composites fabricated by Zhang et al exhibited enhanced EMW absorption performance composites compared to the composite without MWCNTs. 25 Mo et al reported the 3D CNTs@TiO 2 sponge by hydrolysis and heat treatment method, which exhibited the desired reflection loss.…”
Section: Introductionmentioning
confidence: 98%
“…Three-dimensional (3D) micro-nanomaterials have attracted wide attention because of their unique morphologies, large specific surface area, well-defined interfaces, and abundant pores. To date, various 3D micro-nanomaterials, including metallic foams, graphene foam, Bi 2 WO 6 /graphene hydrogel, nanocellulose aerogel foam, have been fabricated for applications in catalytic reactions, energy storage, and photoelectronic devices. In particular, some 3D micro-nanomaterials such as graphene foam, α-MnO 2 , rGO/α-Fe 2 O 3 hydrogel, MoS 2 nanospheres, Ag@PPy sponge have been developed to attenuate electromagnetic wave (EMW) energy because the interfaces and pores in these 3D micro-nanomaterials could cause additional dielectric losses, which were difficult to be achieved by one-dimensional (1D) and two-dimensional materials. In spite of these advances of the 3D micro-nanomaterials in the attenuation of the EMW energy, several drawbacks are still obvious, which limit their practical applications. First, after being mixed with the matrix, some 3D structural feature remained with difficulty because of unsatisfactory connection interfaces between different components, and thus, the contribution from the 3D interconnected structure to EMW energy attenuation was suppressed greatly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, owing to the large aspect ratio and strong intermolecular forces, MWCNTs were easy to aggregate, which would lead to poor dispersity and conductivity. According to the reports, the good dispersity and high conductivity of MWCNTs were crucial factors to affect the EMA performance. Therefore, much more attention had been paid to improve the dispersity and conductivity of MWCNTs; for example, Stevens group altered the properties of SWCNTs by grating N -alkylidene aminos on their sidewalls.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, MWCNTs belong to dielectric loss absorber materials, and increasing the electronic polarization or interface polarization was a significant strategy to absorb and attenuate the EM wave. In our previous research, polystyrene (PS) microspheres were used to construct three-dimensional (3D) absorbers with MWCNTs via self-assembly. The results suggested that the construction of a 3D structure could enhance the dispersion and conductivity of MWCNTs, which increased the interfacial polarization and led to the improvement of microwave absorption performance of MWCNTs. ,, However, PS microspheres were used in electric insulation, which would block the electronic transmit pathway and lead to the decrease of conductivity; as a result, the microwave absorbing properties of MWCNTs would be reduced.…”
Section: Introductionmentioning
confidence: 99%